Relationships of Healthcare Communication, Emotional Support and Family Support on Hemodialysis Decisions - Dwi Laksono, Rudy; Esah Siti Aisyah; Ana Rosyana; Ike Junita Triwardhani (STIKes Ibnu Sina Ajibarang, 2024)
Hemodialysis is a primary therapy for patients with end-stage chronic kidney disease. This study aims to examine the relationship between healthcare communication, emotional support, and family support on patients' decisions to undergo hemodialysis. A cross-sectional survey method was employed, involving 77 patients at the Hemodialysis Unit of Dustira Hospital, Cimahi. The research instruments included structured questionnaires measuring variables such as healthcare communication, healthcare emotional support, family support, and consent decisions. Data were analyzed using SmartPLS software. The results showed that healthcare communication had a significant influence on emotional support (R = 0.640, p < 0.001) and family support (R = 0.611, p < 0.001). Healthcare communication also had a very strong and significant impact on patients' consent decisions (R = 0.663, p < 0.001). Although the emotional support from healthcare providers had a small impact on consent decisions (R = 0.034, p > 0.05), family support had a relatively small but greater influence (R = 0.108, p < 0.05). In conclusion, effective communication between healthcare providers and family support is crucial in the medical decision-making process for hemodialysis patients. Enhancing the quality of communication between healthcare providers and patients is essential to support better medical decisions and improve patient health outcomes.